Perforated Peptic Ulcer Surgery: Decreased Length of Stay but No Difference in Mortality with Laparoscopic Repair. Issue 6 (December 2018) - Gabriel, Viktor; Grigorian, Areg; Schubl, Sebastian D.; Pejcinovska, Marija; Won, Eugene; Lekawa, Michael; Bernal, Nicole; Nahmias, Jeffry
Abstract : Background: Perforated peptic ulcer (PPU) surgery mortality ranges 1% to 24%. We hypothesized a decrease in length of stay (LOS) with laparoscopic surgical repair (LSR) compared with open surgical repair (OSR). Methods: Patients undergoing PPU surgery 2005 to 2015 were identified in NSQIP. LSR was compared with OSR 2005 to 2015. LSR 2005 to 2010 was compared with 2011 to 2015. OSR 2005 to 2010 was compared with 2011 to 2015. The primary outcome was LOS. Secondary outcomes were mortality and morbidity. Results: Between 2005 and 2015, LSR had a decreased LOS, was more likely to wean from the ventilator, but had no significant difference in mortality compared with OSR. There was no significant difference in mortality for LSR or OSR over time. Conclusions: When patients are appropriately selected, LSR for PPU is a viable alternative to OSR, decreasing LOS and pulmonary complications. This demonstrates significant benefit to patients and hospital throughput. Abstract : Supplemental Digital Content is available in the text.